Peculiarities of I-II Form Pupils’ Creativity in Music Activity - Girdzijauskienė, Rūta (Acta Paedagogica Vilnensia, 2002)
This article presents the scientific research results: the peculiarities of I-II form pupils' creativity at the time they interpret, arrange or evaluate music; emotional experiences in music activity; the peculiarities of activity fluency, flexibility, sagacity, originality expression; I-II form pupils' creativity similarities and differences upbringing in sex and age facets. The data show, that I-II form pupils are the most successful at evaluating music clearly, adequately, in a versatile way, at interpreting music without any constraint, purposefully and expressively they are good at arranging music consistently and variously. This age pupils find it more difficult: to evaluate originally, to perform keenly, to arrange music keenly, accurately, - without any stereotypes. Especially difficult activity is improvisation. In music activity junior schoolchildren feel both positive and negative experience, through positive emotions are experienced much more often. The bigger part of I-II form pupils in music lessons act fluently and flexibly through they are less sagacious and original. Beside, girls are more creative than boys and II form pupils are more creative than l formers.
Keywords: Music lessons; music activity; creativity; emotional experiences.